Broad Clade 2 cross-reactive immunity induced by an adjuvanted clade 1 rH5N1 pandemic influenza vaccine. - Isabel Leroux-Roels (Public Library of Science (PLoS), 2008)
Background The availability of H5N1 vaccines that can elicit a broad cross-protective immunity against different currently circulating clade 2 H5N1 viruses is a pre-requisite for the development of a successful pre-pandemic vaccination strategy. In this regard, it has recently been shown that adjuvantation of a recombinant clade 1 H5N1 inactivated split-virion vaccine with an oil-in-water emulsion-based adjuvant system also promoted cross-immunity against a recent clade 2 H5N1 isolate (A/Indonesia/5/2005, subclade 2.1). Here we further analyse the cross-protective potential of the vaccine against two other recent clade 2 isolates (A/turkey/Turkey/1/2005 and A/Anhui/1/2005 which are, as defined by WHO, representatives of subclades 2.2 and 2.3 respectively). Methods and findings Two doses of the recombinant A/Vietnam/1194/2004 (H5N1, clade 1) vaccine were administered 21 days apart to volunteers aged 18-60 years. We studied the cross-clade immunogenicity of the lowest antigen dose (3.8 microg haemagglutinin) given with (N = 20) or without adjuvant (N = 20). Immune responses were assessed at 21 days following the first and second vaccine doses and at 6 months following first vaccination. Vaccination with two doses of 3.8 microg of the adjuvanted vaccine induced four-fold neutralising seroconversion rates in 85% of subjects against A/turkey/Turkey/1/2005 (subclade 2.2) and 75% of subjects against A/Anhui/1/2005 (subclade 2.3) recombinant strains. There was no response induced against these strains in the non-adjuvanted group. At 6 months following vaccination, 70% and 60% of subjects retained neutralising antibodies against the recombinant subclade 2.2 and 2.3 strains, respectively and 40% of subjects retained antibodies against the recombinant subclade 2.1 A/Indonesia/5/2005 strain. Conclusions In addition to antigen dose-sparing, adjuvantation of inactivated split H5N1 vaccine promotes broad and persistent cross-clade immunity which is a pre-requisite for a pre-pandemic vaccine. Trial registration ClinicalTrials.gov NCT00309634.